Factors associated with status and self-perceived mental health changes in the face of the COVID-19 pandemic in Brazil. - Rander Junior Rosa; Juliana Soares Tenório de Araújo; Thaís Zamboni Berra; Antônio Carlos Vieira Ramos; Heriederson Sávio Dias Moura; Murilo César do Nascimento; Ariela Fehr Tártaro; Ruan Victor Dos Santos Silva; Felipe Mendes Delpino; Regina Célia Fiorati; Titilade Kehinde Ayandeyi Teibo; Yan Mathias Alves; et al. (Public Library of Science (PLoS), 2023)
The SARS-CoV-2-triggered Public Health Emergency of International Importance has significantly contributed to emotional and mental health issues. The aim of this study was to identify factors associated with self-perceived mental health changes while facing the COVID-19 pandemic in Brazil. This was a cross-sectional, descriptive, and analytical study that collected data via a web survey using a validated instrument. The study included individuals over 18 years old residing in the 26 federal units and the Federal District from August 2020 to November 2022. The sample was recruited using the snowball technique. Two logistic regression analyses were conducted to identify factors associated with the outcomes of interest. The first analysis considered individuals who rated their mental health condition as poor as the dependent variable, while the second analysis considered individuals who reported changes in their mental health during the pandemic as the dependent variable. The study found that individuals with complete college education and those using tranquilizers or antidepressants were more likely to perceive their mental health as poor (1.97 and 2.04 times higher likelihood, respectively). Increased consumption of ultra-processed foods during the pandemic was associated with a 2.49 higher likelihood of reporting mental health changes. Participants also reported more difficulty sleeping. The negative self-perception of mental health varied across Brazil's regions and changed over time, with different patterns observed before and after the vaccination period. In 2022, most regions of Brazil classified their mental health as "poor." The study highlights the impact of the COVID-19 pandemic on mental health, with increased prevalence of mental disorders and emotional problems among the population. The results highlight the presence of mental disorders and increased reporting of emotional problems among the population due to the impact of the COVID-19 pandemic.